2023
DOI: 10.1002/lio2.1010
|View full text |Cite
|
Sign up to set email alerts
|

Hearing health care access for adult cochlear implant candidates and recipients: Travel time and socioeconomic status

Abstract: Objectives: Access to cochlear implantation may be negatively influenced by extended travel time to a cochlear implant (CI) center or lower socioeconomic status (SES) for the individual. There is a critical need to understand the influence of these variables on patient appointment attendance for candidacy evaluations, and CI recipients' adherence to post-activation follow-up recommendations that support optimal outcomes. Methods: A retrospective chart review of adult patients referred to a CI center in North C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the US, several studies showed that non-Caucasians pursued CIs at a lower rate but qualified for CIs at higher rates (69,27,49). In multiple countries, socioeconomic status and education level were found to be factors in CI uptake (28,34,51,62). Eligible adults with higher incomes and higher education levels were more likely to pursue a CI.…”
Section: Resultsmentioning
confidence: 99%
“…In the US, several studies showed that non-Caucasians pursued CIs at a lower rate but qualified for CIs at higher rates (69,27,49). In multiple countries, socioeconomic status and education level were found to be factors in CI uptake (28,34,51,62). Eligible adults with higher incomes and higher education levels were more likely to pursue a CI.…”
Section: Resultsmentioning
confidence: 99%
“…However, our data showed that no matter what their employment status (employed/retired/unemployed/disabled) was, it did not affect the OR of receiving the CI surgery. Davis et al (10) looked at a similar socioeconomic proxy using the zip code tabulation area-level social deprivation index. The authors noted that this correlated with whether or not they attended their CI candidacy evaluation appointment (10).…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al (10) looked at a similar socioeconomic proxy using the zip code tabulation area-level social deprivation index. The authors noted that this correlated with whether or not they attended their CI candidacy evaluation appointment (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nassiri et al found that among adults, there was an association between greater travel distances and older age at the time of cochlear implantation ( 13 ). Additionally, Davis et al ( 14 ) observed a significant difference in socioeconomic position (SEP) between patients who attended and did not attend the evaluation appointment for cochlear implantation. Although travel time did not differ significantly between the two groups, there was a significant interaction between SEP and geographic location in North Carolina, where rural counties were farther from the cochlear implant center and were also more likely to be associated with lower SEP.…”
Section: Introductionmentioning
confidence: 99%